2021
DOI: 10.1093/jxb/erab028
|View full text |Cite
|
Sign up to set email alerts
|

Smart glass impacts stomatal sensitivity of greenhouse Capsicum through altered light

Abstract: Optical films that alter light transmittance may reduce energy consumption in high-tech greenhouses, but their impact on crop physiology remains unclear. We compared the stomatal responses of Capsicum plants grown hydroponically under control glass (70% diffuse light) or smart glass (SG) film ULR-80, which blocked >50% of short-wave radiation and ~9% of photosynthetically active radiation (PAR). SG had no significant effects on steady-state (gs) or maximal (gmax) stomatal conductance. In contrast, SG re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 77 publications
(115 reference statements)
0
14
0
Order By: Relevance
“…The experiment was conducted in a controlled environment greenhouse facility with east–west orientation located on the Hawkesbury Campus of Western Sydney University, Richmond, NSW, Australia. The four research bays (105 m 2 each) were fitted with HD1AR diffuse glass (70% haze, roof; 5% haze, wall), as previously described [ 13 , 59 ]. Two bays with diffuse glass were designated control bays and two bays (roof and side walls) were coated with SGF (ULR-80, Solar Gard, Saint-Gobain Performance Plastics, Sydney, Australia) and designated as treatment bays.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was conducted in a controlled environment greenhouse facility with east–west orientation located on the Hawkesbury Campus of Western Sydney University, Richmond, NSW, Australia. The four research bays (105 m 2 each) were fitted with HD1AR diffuse glass (70% haze, roof; 5% haze, wall), as previously described [ 13 , 59 ]. Two bays with diffuse glass were designated control bays and two bays (roof and side walls) were coated with SGF (ULR-80, Solar Gard, Saint-Gobain Performance Plastics, Sydney, Australia) and designated as treatment bays.…”
Section: Methodsmentioning
confidence: 99%
“…The facility included four experimental bays (105 m 2 each) fitted with HD1AR diffuse glass on the roof (70% haze) and on the sidewall (5% haze). Two bays were coated with SG film (Solar Gard, Saint-Gobain Performance Plastics, Sydney, Australia) on both roof and side walls and the other two bays were used as "Control' as described previously (Chavan et al 2020;Zhao et al 2021). To investigate the effect of SG and time of planting on capsicum, a 2×2 factorial design was adopted with two cultivars, Orange included six gutters that were 10.8 m (length) × 25 cm (width, AIS Greenworks, Castle Hill, NSW, Australia), and contained 10 Rockwool slabs (90×15×10 cm, Grodan, The Netherlands) as a substrate for plants, per gutter.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…Studies investigating the impact of cover materials are not generally conducted at a commercial scale (Loik et al, 2017; Shen et al, 2021) nor do they comprehensively assess plant growth responses to altered light regimes caused by seasonal change or reduction in PAR (Aroca-Delgado et al, 2019). Recently, we have investigated the impact of light changes on crop growth, photosynthesis, yield, post-harvest fruit quality, and energy assessment using commercial practices of greenhouse vegetable production of eggplant and capsicum in a research facility with the precise climate control of a high-tech commercial glasshouse (Chavan et al, 2020; He et al, 2021, 2022; Lin et al, 2022; Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers across continents have compared the energy use between open field cultivation and protected cropping [12][13][14][15]. They have also investigated various heat-filtering film coverings for greenhouse crop production [16][17][18] and developed prediction models of protected cropping energy consumption [19][20][21][22]. These investigations have shown consistent results in response to the effective management of energy consumption through temperature prediction, the introduction of new greenhouse covering materials, glass coatings, and the use of renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…[16,18] concluded that "Smart Glass" film (commercially available window film ULR-80 that blocks UV and higher light wavelengths which are not used for plant growth but contribute to heat generation) applied to the roof and walls of a greenhouse increase energy and resource use efficiency, without affecting fruit quality. The energy saving was accompanied by certain levels of yield reduction in both eggplant and capsicum crops [16,18]. However, there is still a lack of research investigation on energy analysis in protected cropping from adjustable ventilation and energy-efficient design perspectives.…”
Section: Introductionmentioning
confidence: 99%